The Y chromosomal fertility factor threads in Drosophila hydei harbors a functional gene encoding an axonemal dynein beta heavy chain protein. - Kurek, R.; Reugels, A.M.; Glatzer, K.H.; Bunemann, H. (Genetics, 1998)
To understand the contradiction between megabase-sized lampbrush loops and putative protein encoding genes both associated with the loci of Y chromosomal fertility genes of Drosophila on the molecular level, we used PCR-mediated cloning to identify and isolate the cDNA sequence of the Y chromosomal Drosophila hydei gene DhDhc7(Y). Alignment of the sequences of the putative protein DhDhc7(Y) and the outer arm dynein beta heavy chain protein DYH2 of Tripneustes gratilla shows homology over the entire length of the protein chains. Therefore the proteins can be assumed to fulfill orthologous functions within the sperm tail axonemes of both species. Functional dynein beta heavy chain molecules, however, are necessary for the assembly and attachment of outer dynein arms within the sperm tail axoneme. Localization of DhDhc7(Y) to the fertility factor Threads, comprising at least 5.1 Mb of transcriptionally active repetitive DNA, results from an infertile Threads- mutant where large clusters of Threads specifically transcribed satellites and parts of DhDhc7(Y) encoding sequences are missing simultaneously. Consequently, the complete lack of the outer dynein arms in Threads- males most probably causes sperm immotility and hence infertility of the fly. Moreover, preliminary sequence analysis and several other features support the hypothesis that DhDhc7(Y) on the lampbrush loops Threads in D. hydei and Dhc-Yh3 on the lampbrush loops kl-5 in Drosophila melanogaster on the heterochromatic Y chromosome of both species might indeed code for orthologous dynein beta heavy chain proteins.